Improving Social Sensitivity for Gen Z Through Family Counseling Guidance - Sipahutar, Melina Agustina; Hutahaean, Agnes Novianti; Manalu, Goklas J; Lestari, Lidwina (Jurnal Ilmu Sosial Mamangan, 2025)
This research aims to increase the social sensitivity of Generation Z (Gen Z) through family counseling, with a focus on the Pahae Julu District area. Gen Z's social sensitivity has decreased due to the influence of technology and lack of social interaction in the surrounding environment. The family has an important role in instilling social values, but is often neglected because parents are busy at work. This research uses descriptive qualitative methods, with data collection techniques through interviews, observation and documentation. This research concludes that family counseling guidance is very necessary to help parents educate Gen Z children, as well as to strengthen social values in their lives.  The output of this research is outlined in the family counseling guidance module designed in this research which includes material regarding courtesy, empathy, individualism, and identity crises that are often faced by Gen Z. This research has an impact on the design of the module which uses open discussion strategies, reflection, and practical activities to increase feelings of empathy and social responsibility